(untitled) (Journal of Population and Development, 2022)
All countries have to face population aging sooner or later, depending on their degree of development. However, elderly care is predicted to soon become a major concern for developing countries such as Nepal. Both quantitative and qualitative investigations were conducted on elderly people living in Pashupati Elderly’s Home in Kathmandu using the descriptive and eresearch design. Thirty elderly people were the respondents of this study. Face-to-face interview, KII, and observation methods were used to collect data on the elderly and their attitudes toward senior citizen homes. Most elderly people are forced by different factors like loneliness, family dispute, disability, poverty, and domination in their families to take shelter in old people’s homes for several years. Some were living happily in the home, though they missed their family on some occasions because they could have spent their leisure time by sharing their emotions and feelings with same-age groups.